2008
DOI: 10.1080/17453670710015058
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave therapy for chronic Achilles tendinopathy: A double-blind, randomized clinical trial of efficacy

Abstract: Interpretation Extracorporal shock-wave therapy appears to be a supplement for the treatment of chronic Achilles tendinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
155
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 35 publications
7
155
0
5
Order By: Relevance
“…Patients were followed up at 4, 8, and 12 weeks. AOFAS increased more over time in the intervention group than in the control, from 74 to 81 in the placebo group and from 70 to 88 in the intervention group [34]. Better results were seen in the intervention group at 8 and 12 weeks follow-up.…”
Section: Extracorporeal Shock Wave Therapysupporting
confidence: 48%
See 2 more Smart Citations
“…Patients were followed up at 4, 8, and 12 weeks. AOFAS increased more over time in the intervention group than in the control, from 74 to 81 in the placebo group and from 70 to 88 in the intervention group [34]. Better results were seen in the intervention group at 8 and 12 weeks follow-up.…”
Section: Extracorporeal Shock Wave Therapysupporting
confidence: 48%
“…Interestingly, women showed the best outcome, an unexpected finding. The authors concluded that ESWT appears to be a supplement for the treatment of chronic Achilles tendinopathy [34].…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…6 -10, 13 With good clinical success rates, indications of this treatment have expanded to other tendinopathies. 6 There are several theories for explaining the mechanism of shock wave effect in various cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous materials and agents have been used as a mechanical barrier to envelop sutured tendons in attempts to minimize the adhesion formation after primary tendon repair. Currently, the modalities used for preventing adhesions without affecting the healing process include; human amniotic fluid, hyaluronic acid, alginate solution, mannose-6-phosphate, 5-fluorouracil, injection of growth factors or platelet concentrate, local application of extracorporeal shock wave therapy or ultrasound therapy, local injection of bone-marrow-derived mesenchymal stem cells, systemic administration of antiinflammatory drugs [7][8][9][10][11][12][13][14][15][16] . The use of a barrier during surgery to protect raw tissue surfaces has been shown to be one of the most effective methods of preventing tendon adhesions.…”
Section: Introductionmentioning
confidence: 99%